The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/0074-02760160254
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of LAMP and PCR for molecular mass screening of sand flies for Leishmania martiniquensis infection

Abstract: BACKGROUND Leishmaniasis caused by Leishmania martiniquensis infection has been reported in human and domestic animals of Martinique Island, Germany, Switzerland, USA, Myanmar and Thailand. The peculiar clinical features of disseminated cutaneous and visceral forms co-existence render the urgent need of specific diagnostic tool to identify the natural sand fly vectors for effective prevention and control strategies. Loop-mediated isothermal amplification (LAMP) of 18S rRNA gene as well as polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…martiniquensis from ‘ L . siamensis ’ (MHOM/TH/2010/TR) but the size of PCR products could not differentiate parasites in other subgenera [ 28 ]. For the ITS1-PCR method, it is not suitable for the discrimination of ‘ L .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…martiniquensis from ‘ L . siamensis ’ (MHOM/TH/2010/TR) but the size of PCR products could not differentiate parasites in other subgenera [ 28 ]. For the ITS1-PCR method, it is not suitable for the discrimination of ‘ L .…”
Section: Discussionmentioning
confidence: 99%
“…orientalis ) and L . martiniquensis infection as it generates the same size of products [ 1 , 28 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,40 Our results differed from those reported by Adams et al 10 with a LoD of 1 × 10 2 parasites/mL for L. donovani and Sriworarat et al 14 with a LoD of 1 × 10 3 parasites/mL for Leishmania siamensis in whole blood samples. In addition, a report by Tiwananthagorn et al 58 concluded that a PCR-kDNA assay was more sensitive than PCR-ITS and LAMP with the 18S rRNA gene. 42 Therefore, a comprehensive study to evaluate these parameters in a vast set of Leishmania species causing CL in the New World is needed.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study also experimentally validated the potential field applicability of the MG-LAMP for detection of L . martiniquensis DNA in sand flies in Thailand; however, no Leishmania DNA was detected by LAMP and PCR when applied to 380 field-caught flies, probably due to low infection rate in the study area [79]. Additionally, the performance of the MG-LAMP was further validated using purified DNA from sand fly pools and was found to be of potential use for the entomological surveillance of CL in Colombia with 100% sensitivity and 96.8% specificity [80].…”
Section: Molecular Xenomonitoring/surveillance Potentials Of Lamp Formentioning
confidence: 99%